2016
DOI: 10.1016/j.neuropsychologia.2016.03.028
|View full text |Cite
|
Sign up to set email alerts
|

The influence of unilateral contraction of hand muscles on the contralateral corticomuscular coherence during bimanual motor tasks

Abstract: The mechanisms behind how muscle contractions in one hand influence corticomuscular coherence in the opposite hand are still undetermined. Twenty-two subjects were recruited to finish bimanual and unimanual motor tasks. In the unimanual tasks, subjects performed precision grip using their right hand with visual feedback of exerted forces. The bimanual tasks involved simultaneous finger abduction of their left hand with visual feedback and precision grip of their right hand. They were divided into four conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…After the iMVC test, each individual was instructed to conduct finger extension and flexion motions according to the same limb configuration presented in Figure 1A at different contraction levels. According to previous studies (19,36,37), constant and moderate (contraction level<50%) muscle contraction can demonstrate the most pronounced CMCoh in the Beta band range without the subject suffering from significant muscle fatigue, with less spontaneous discharges of muscles during the contraction compared with higher levels. The potential residual spontaneous discharges in the recorded EMG were further reduced by the baseline removal in Equation 1.…”
Section: Isometric Finger Extension/flexion Tasksmentioning
confidence: 84%
“…After the iMVC test, each individual was instructed to conduct finger extension and flexion motions according to the same limb configuration presented in Figure 1A at different contraction levels. According to previous studies (19,36,37), constant and moderate (contraction level<50%) muscle contraction can demonstrate the most pronounced CMCoh in the Beta band range without the subject suffering from significant muscle fatigue, with less spontaneous discharges of muscles during the contraction compared with higher levels. The potential residual spontaneous discharges in the recorded EMG were further reduced by the baseline removal in Equation 1.…”
Section: Isometric Finger Extension/flexion Tasksmentioning
confidence: 84%
“…Thus, it may be speculated that increasing the corticomuscular coupling strength of the paretic limb for stroke patients is both the goal and the way for regaining motor function. Many factors have been identified to influence the corticomuscular coupling strength and some of them have the potential to be utilized in limb rehabilitation interventions ( 11 ). Above all, the results of the current study remind us that exploring the influence of rehabilitation interventions on corticomuscular coupling may provide another way to verify their validity from a new point.…”
Section: Discussionmentioning
confidence: 99%
“…An elbow flexion task was designed for the stroke patient because only poor rehabilitation outcomes can be generally obtained for hand. The force applied by the elbow flexion was monitored by a strain gage and fed back to the patient visually to help him finish the task with moderate and constant muscle contractions ( 11 ), because coherence analyses ( 12 , 13 ) have demonstrated that the coupling is most pronounced in the beta-band range during steady muscle contractions and the beta-band CMC is assumed to be associated with strategies for controlling submaximal muscle forces ( 12 , 14 , 15 ). The designed motion task and the visual feedback information on screen are illustrated in Figures 1 A,B, respectively.…”
Section: Backgroundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study did not include dedicated measurements of the kinematic profiles of finger flexion/extension movements. In terms of behavioral correlates, the cortico-muscular coherence should be studied to assess the coupling between EEG signals and voluntary muscle discharges (Larsen et al, 2016; Zheng et al, 2016). …”
Section: Discussionmentioning
confidence: 99%